2007
DOI: 10.1037/0021-843x.116.3.448
|View full text |Cite
|
Sign up to set email alerts
|

Memory for emotionally neutral information in posttraumatic stress disorder: A meta-analytic investigation.

Abstract: Studies have come to conflicting conclusions about whether posttraumatic stress disorder (PTSD) is associated with poorer memory for emotionally neutral information. The authors report a meta-analysis of 27 studies that investigated verbal and/or visual memory in samples with PTSD and healthy controls. The results indicated that the association between PTSD and memory impairment appears to be robust, small to moderate in size, and stronger for verbal than for visual memory. Effect sizes did not vary according … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

33
211
5
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 261 publications
(254 citation statements)
references
References 73 publications
33
211
5
5
Order By: Relevance
“…Brewin et al (2007) found that the overall magnitude of the association was small to moderate, and was stronger for verbal than for visual memory, affecting immediate and delayed recall equally, even after controlling for the presence of concurrent head injuries. Johnsen and Asbjørnsen (2008) examined verbal memory only and found a medium effect comparing people with PTSD to normal controls.…”
Section: Memorymentioning
confidence: 87%
See 2 more Smart Citations
“…Brewin et al (2007) found that the overall magnitude of the association was small to moderate, and was stronger for verbal than for visual memory, affecting immediate and delayed recall equally, even after controlling for the presence of concurrent head injuries. Johnsen and Asbjørnsen (2008) examined verbal memory only and found a medium effect comparing people with PTSD to normal controls.…”
Section: Memorymentioning
confidence: 87%
“…People with PTSD appear to process threat-related stimuli differently than neutral stimuli (for reviews, see Bar-Haim, Lamy, Pergamin, Bakermans-Kraneburg, & van IJzendoom, 2007;Buckley, Blanchard, & Neill, 2000;Constans, 2005). In addition, studies utilizing neuropsychological tests involving emotionally neutral information (e.g., words or photographs that do not evoke any particular emotional content) have shown that PTSD is most robustly associated with impairments on tasks assessing overall intellectual ability, attention, memory, and executive functioning (Vasterling, Verfaellie, & Sullivan, 2009;Vasterling & Brailey, 2005;Johnson & Asbjørnsen, 2008;Brewin, Kleiner, Vasterling, & Field, 2007;Brewin, Andrews, & Valentine, 2000). Although neuropsychological impairment associated with PTSD is typically mild to moderate in magnitude, often falling within the normal range, these impairments may be of high clinical relevance .…”
Section: Neuropsychology Of Ptsdmentioning
confidence: 99%
See 1 more Smart Citation
“…Addressing this request is often challenging due to the complexity of coincident non-concussive conditions that may negatively impact cognitive functioning. Post-traumatic stress (Brewin, Kleiner, Vasterling, & Field, 2007;Marx et al, 2009), depression (cf., Vasterling et al, 2006;Zakzanis, Leach, & Kaplan, 1998), and other Axis I comorbidities may contribute to varied cognitive difficulties and obscure whether cognitive limitations reflect concussion history. Moreover, chronic ''post-concussive'' symptoms (PCS) are highly non-specific and cannot be reliably linked with concussion itself.…”
Section: Introductionmentioning
confidence: 99%
“…Bremner, Vermetten, Afzal, & Vythilingam, 2004). A meta-analysis confirms that subsequent to an interpersonal trauma, individuals suffering from PTSD show verbal memory deficits compared to non-PTSD participants (Brewin, Kleiner, Vasterling, & Field, 2007). Trauma exposure may also be associated with lower performance on episodic memory tests, even independently of PTSD (Johnsen & Asbjørnsen, 2008; Rivera-Vélez, González-Viruet, Martínez-Taboas, & Pérez-Mojica, 2014).…”
Section: Introductionmentioning
confidence: 80%